STRATEGI PEMASARAN USAHA KECIL DAN MENENGAH - Triyaningsih, Sri Lestari (Universitas Slamet Riyadi, 2012)
ABSTRACT Marketing strategy is very important for a company where marketing strategy is a way of achieving the goal of a company. So also in small and medium enterprises need to implement a marketing strategy. Problems faced by small and medium enterprises for this are: 1) lack of capital to develop the business, 2) marketing strategy, and 3) the dependence of micro high enough to season and market demand, causing the business to be volatile and difficult to develop. To overcome the above problems, particularly in the implementation of small to medium enterprise marketing strategy, then things can be done is to do: 1) market segmentation, in designing a product, small and medium businesses have to run the market segmentation. By segmenting the market, small and medium businesses can better optimize each product release. 2) Cooperation among small and medium businesses. Cooperating with other small and medium businesses as well needs to be done in order to strengthen mutual efforts. Keywords: Marketing strategies, Â small and medium enterprises